Odpowiedzi

2010-02-07T20:11:55+01:00
A) = 6a + 2b - 2a + b = 4a + b
b) = 2x - 2 - 2x = 2
c) = x² - x - 3x² + 3x = -2x² - 2x
d) = 5a² - 15a - 3a² + 15a = 2a²
e) = 3x² + xy - xy + y = 3x² + y
;))
5 3 5
2010-02-07T20:13:42+01:00
2(3a + b) - 2(a-b) = 6a + 2b - 2a + 2b = 4a + 4b
1/2(4x - 4) - 2x = - 2
x(x - 1) - 3(x² - x) = x² - x - 3x² + 3x = -2x² + 2 x
5a(a - 3 ) - 3a (a - 5) = 5a² - 15a - 3a² + 15a = 2a²
3x (x + 1/3y) - 2y (1/2x - 1/2) = 3x² + xy - xy + y = 3x² + y


3 3 3
2010-02-07T20:14:46+01:00
2(3a + b) - 2(a-b)=6a + 2b - 2a + 2b = 4a + 4b
1/2(4x - 4) - 2x =2x - 2 - 2x = -2
x(x - 1) - 3(x² - x)=x² - x - 3x² + 3x = -2x² + 2x
3x (x + 1/3y) - 2y (1/2x - 1/2) = 3x² +3xy - xy + y = 3x² + 2xy + y
5a(a - 3 ) - 3a (a - 5) = 5a² - 15a - 3a² + 15a +15a = 2a² + 15a

2 1 2